Adjustment of Soil Saturated Paste Extract Electrical Conductivity and Sodium Adsorption Ratio for Excess Gypsum Dissolution Using Equilibrium Geochemical Modeling. Issue 4 (14th July 2016) - Callaghan, Michael V.; Cey, Edwin E.; Bentley, Laurence R.
Abstract : Core Ideas: In gypsum‐bearing soils, excess dissolution occurs in the soil saturated paste extract. EC and SAR may be adjusted for dissolution effects using geochemical modeling. Characterization of salinity and sodicity hazard is improved. Soil saturated paste extract (SPE) electrical conductivity (ECe ) and sodium adsorption ratio (SARe ) are widely used measures of soluble salts used to evaluate the salinity hazard to crop growth and the sodicity hazard to soil permeability. In gypsum‐bearing soils, sparingly soluble gypsum dissolves during preparation of the SPE as a result of soil water dilution. This produces a higher measured ECe and lower SARe than would be measured if only field‐soluble gypsum were present. As part of a soil remediation project, samples were collected from the location of a former oil and gas production facility with highly saline‐sodic, brine‐affected soils. The naturally calcareous silt loam soil with a smectitic clay fraction was previously amended with gypsum to mitigate elevated sodicity, of concern for sodic effects on soil permeability. The equilibrium geochemical modeling software program ExtractChem was used to model ECe and SARe in the absence of excess gypsum dissolution by first modeling EC and SAR at field water content and then modeling ECe and SARe at saturated paste water content while excluding gypsum from the modeled reaction. For samples with measured ECe <3 dS m −1, ECe modeled in the absence of excess gypsum dissolution was up to 52% lower than measured, and for samples with measured SARe <2, modeled SARe was up to 53% higher than measured. As remediation progressed, and ECe and SARe decreased toward target values, the magnitude of the excess gypsum effect was sufficient to affect the evaluation of remedial progress. Equilibrium geochemical modeling adjustment of ECe and SARe for gypsum dissolution that occurs as a result of SPE preparation is recommended to improve the evaluation of the progress of remediation of gypsum‐bearing, salt‐affected soil.